SPECIFIC ASPECTS OF THE PROGRAMMING AND ROMANTIC PLOTS IN THE FORTEPIANO CREATION OF FERENCE LIST - Allaniyazova , Gulnara Kutlimuratovna; Karimova , Gulnora Soliyevna; Temirova , Ra’no Muhiddinovna (Educational Research in Universal Sciences, 2023)
Romantic programming in the piano works of Ferenc Liszt was described practically and theoretically.